Analogi Mitos “Weri Ata” dan Kurban Salib Kristus untuk Mencari dan Menemukan Profil Agen Pastoral yang Berciri Dedikatif dan Inovatif - Marselus Kur (STIPAS St. Sirilus Ruteng, 2012)
The studyand the process of Inculturation is a pastoral imperative in the Church. There are principles how to guide the process of Inculturation among others that Inculturation presupposes indeed the Cultural Intelligence with all its aspects or elements. The knowledge about cultural contexts and at the sametime about the richness of the Gospel that has been never cultural free in the history of the Church is a core necessity for the Church.This article is dealing a lot with this process of Inculturation, a dialogue between local heritage called “Weri Ata